2020
DOI: 10.3892/ol.2020.11802
|View full text |Cite
|
Sign up to set email alerts
|

Genistein inhibits lung cancer cell stem‑like characteristics by modulating MnSOD and FoxM1 expression

Abstract: Manganese superoxide dismutase (MnSOD) promotes invasive and migratory activities by upregulating Forkhead box protein M1 (FoxM1) expression. The present study investigated whether modulation of MnSOD and FoxM1 expression was responsible for the antitumor effects of genistein on cancer stem-like cells (CSLCs) derived from non-small cell lung cancer cells (NSCLCs). Spheroids prepared from H460 or A549 cells were defined as lung cancer stem-like cells (LCSLCs) and were treated with genistein. The Cell Counting K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Additionally, previous studies reported that genistein could induce cell cycle arrest and apoptosis in NSCLC cells 36,37 . Moreover, genistein could repress the stem‐like characteristics in NSCLC cells 26 . These studies implied the anti‐tumor function of genistein in NSCLC.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Additionally, previous studies reported that genistein could induce cell cycle arrest and apoptosis in NSCLC cells 36,37 . Moreover, genistein could repress the stem‐like characteristics in NSCLC cells 26 . These studies implied the anti‐tumor function of genistein in NSCLC.…”
Section: Discussionmentioning
confidence: 72%
“…36,37 Moreover, genistein could repress the stem-like characteristics in NSCLC cells. 26 These studies implied the anti-tumor function of genistein in NSCLC. Similarly, we also found the inhibitive function of genistein in NSCLC progression via inhibiting cell growth and metastasis.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Genistein, a flavonoid from soy, was able to suppress migration and invasion of lung cancer stem-like cells (LCSLCs) derived from NSCLC cells by regulating the expression of manganese superoxide dismutase (MnSOD) and Forkhead box protein M1 (FoxM1) (87). Hesperidin can be extracted from citrus fruits and a study proposed that its inhibitory properties on migration and invasion occur via mediation of the SDF-1/CXCR-4 signaling cascade by reducing the secretion of stromal cell-derived factor 1 (SDF-1), resulting in a decrease in CXCR-4, p-p65, p-IκB, and p-Akt.…”
Section: Flavonoidsmentioning
confidence: 99%